2010
DOI: 10.1677/joe-09-0461
|View full text |Cite
|
Sign up to set email alerts
|

Obesity induced by high-fat diet promotes insulin resistance in the ovary

Abstract: Besides the effects on peripheral energy homeostasis, insulin also has an important role in ovarian function. Obesity has a negative effect on fertility, and may play a role in the development of the polycystic ovary syndrome in susceptible women. Since insulin resistance in the ovary could contribute to the impairment of reproductive function in obese women, we evaluated insulin signaling in the ovary of high-fat diet-induced obese rats. Female Wistar rats were submitted to a high-fat diet for 120 or 180 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
57
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 55 publications
11
57
4
1
Order By: Relevance
“…Egr-1 has previously been shown to play a key regulatory role in the ovulation process and localized to granulosa cells of preovulatory and antral follicles after human chorionic gonadotropin stimulation in normal-weight rats (14). Prior studies by Akamine et al (2) and Nteeba et al (39) established that long exposure to high-fat diet in both rats and mice can lead to a similar reduction in PI3K and Akt phosphorylation in whole ovarian tissue, as seen in the current study compared with lean controls. Results from the present study demonstrate that insulin signaling may be affected by obesity; however, additional studies leveraging insulin challenges or hyperinsulinemic euglycemic clamps are warranted to confirm whether ovaries are insulin resistant in this model (2,66).…”
Section: Discussionmentioning
confidence: 99%
“…Egr-1 has previously been shown to play a key regulatory role in the ovulation process and localized to granulosa cells of preovulatory and antral follicles after human chorionic gonadotropin stimulation in normal-weight rats (14). Prior studies by Akamine et al (2) and Nteeba et al (39) established that long exposure to high-fat diet in both rats and mice can lead to a similar reduction in PI3K and Akt phosphorylation in whole ovarian tissue, as seen in the current study compared with lean controls. Results from the present study demonstrate that insulin signaling may be affected by obesity; however, additional studies leveraging insulin challenges or hyperinsulinemic euglycemic clamps are warranted to confirm whether ovaries are insulin resistant in this model (2,66).…”
Section: Discussionmentioning
confidence: 99%
“…These results together indicated that FoxO3a may be an important regulatory factor involved in the ovarian follicular development of HFD-fed mice. Obesity is currently the major factor that causes type 2 diabetes, cardiac malformation and infertility (1). With the increasing epidemic of obesity, a useful mouse model of obesity is essential for studying the mechanisms that underlie the negative effects of obesity negatively on the function of the ovary.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is associated with high rates of type 2 diabetes mellitus, cardiovascular disease and infertility (1,2). The Nurses' Health study reported that a high body mass index (BMI) value is associated with a high risk of infertility in women (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a case in point, increased insulin levels have been associated with increased prolactin secretion 96 and decreased growth hormone secretion pulses 97 . Furthermore, studies using a diet-induced insulin resistance rat model have found increased insulin and progesterone levels 98 . Also, we have previously reported the co-regulated expression levels of insulin, growth hormone, leptin and cortisol in first onset schizophrenia patients, using a targeted analyte cluster method which detects patterned behavior 99 .…”
Section: Effects On the Insulin Signalling And The Hpa Axis In Schizomentioning
confidence: 99%